Logistics costs in Iceland - Mandana Emad 1996- (2022)
Today's economic climate is more dynamic, and governments recognize that globalization has made the world smaller and more competitive. Customers also look for items and services that may meet their individual demands. Companies concentrate on logistics since they fundamentally add expenses to material manufacturing, whereas the cheapest solutions may reduce a company's production performance. It's critical to evaluate logistics expenses and performance in order to figure out how to reduce costs and enhance overall production efficiency. Logistics cost management is becoming extremely crucial in company activities since they account for between ten and fifteen per cent of income. Countries should have reliable statistics in transportation and inventory parts to calculate national logistics costs. Estimating logistics costs is challenging without this knowledge, and the findings are inaccurate. The research attempts to review the literature of the importance and difficulty of estimating logistics costs and measurement with different methods, primarily focused on questionnaire- based surveys and identifying the most critical cost components. As no previous literature was found in measuring the logistics costs in Iceland using a survey, a framework and survey have been designed through this study that covers essential and suitable parameters in measuring logistics costs. Also, the classification of industries has been reviewed and the importance of different industry sectors has been discussed. Further research can conduct the survey, and the survey's results can be compared to logistics costs as a percentage of GDP calculated from national freight transport between regions and international trade. Also, the survey's findings could indicate how the chosen parameters help the companies in Iceland define their flaws and take action about them to reduce their costs effectively to improve profitability and competitiveness. Efnahagsástand nútímans er virkara en áður, og ýmis stjórnvöld viðurkenna að hnattvæðing hefur ...